2017
DOI: 10.1177/1759091417720583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intron 1 Sequences on Human PLP1 Expression: Implications for PLP1-Related Disorders

Abstract: Alterations in the myelin proteolipid protein gene (PLP1) may result in rare X-linked disorders in humans such as Pelizaeus–Merzbacher disease and spastic paraplegia type 2. PLP1 expression must be tightly regulated since null mutations, as well as elevated PLP1 copy number, both lead to disease. Previous studies with Plp1-lacZ transgenic mice have demonstrated that mouse Plp1 (mPlp1) intron 1 DNA (which accounts for slightly more than half of the gene) is required for the mPlp1 promoter to drive significant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Consequently, TM4SF1, TNFSF10, and PLP1 were identified, in which only PLP1 was significantly upregulated as verified by RT-qPCR. PLP1 is the most abundant protein of myelination (Eng et al, 1968;Norton and Poduslo, 1973;Wight, 2017), and the mutation of PLP1 can lead to the X-chromosome-linked leukodystrophy Pelizaeus-Merzbacher disease (Elitt et al, 2020). PLP1 has been widely reported in the formation of the central nervous system while the aberrant expression of PLP1 in various malignant tumors was identified by the bioinformatic analysis (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, TM4SF1, TNFSF10, and PLP1 were identified, in which only PLP1 was significantly upregulated as verified by RT-qPCR. PLP1 is the most abundant protein of myelination (Eng et al, 1968;Norton and Poduslo, 1973;Wight, 2017), and the mutation of PLP1 can lead to the X-chromosome-linked leukodystrophy Pelizaeus-Merzbacher disease (Elitt et al, 2020). PLP1 has been widely reported in the formation of the central nervous system while the aberrant expression of PLP1 in various malignant tumors was identified by the bioinformatic analysis (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our result suggested that the hypomethylation of PLP1 might be involved in the pathophysiology of UFs, but further experiments still need to implement. Moreover, overexpressed PLP1 exhibited major oxidative phosphorylation deficits ( Wight, 2017 ) and the down-regulation of oxidative phosphorylation aggravates therapeutically adverse tumor hypoxia ( Ashton et al, 2018 ). According to our result that the 22 DEGs including PLP1 were enriched in hypoxia, we constructed the posits that PLP1 might participate in the hypoxia program to onset the fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…PLP is important for communication between oligodendrocytes and axons served a neuroprotective role. It is required for proper sequestration of proteins into the myelin compartment, allegedly important for axo-glial metabolism and long-term support of axon [38]. Plp-null mice exhibited severe early-onset thermal hyperalgesia, in the absence of thermal allodynia with late onset central demyelination [39].…”
Section: Discussionmentioning
confidence: 99%
“…The idea that PLP1 might have more than a structural role was understood after it was known that the Plp1 gene was active long before the beginning of myelination [ 46 , 61 ]. In addition, Plp1 gene products have been detected in CNS non-myelinating cells, for instance, in olfactory ensheathing cells [ 62 ], brainstem neurons [ 63 ], cerebellum, and hippocampus neurons [ 64 ], and satellite cells [ 65 ]. Furthermore, neuronal PLP isoforms have been detected during human fetal development that is addressed as classical PLP proteins to the plasma membrane [ 66 ].…”
Section: Proteolipid Protein 1: Substantial Physiological Functionsmentioning
confidence: 99%